2013
DOI: 10.1186/1743-7075-10-42
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic- and sex-specific associations between plasma fatty acids and markers of insulin resistance in healthy young adults

Abstract: BackgroundAlthough evidence indicates that fatty acids (FA) can affect insulin resistance (IR), not all FA contribute equally to the process. Indeed, monounsaturated FA (MUFA) and polyunsaturated FA (PUFA) are reported to reduce IR, whereas saturated FA (SFA) and trans FA appear to increase IR. However, it is not yet clear how individual FA are associated with markers of IR, and whether these relationships are influenced by ethnicity and/or sex. Therefore, the goal of this study was to examine the ethnic- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…suggested that odd‐chained SFA may be negatively associated with T2D, our results indicate this as well . To our knowledge, only one previous study investigated the association between individual FAs and T2D or metabolic markers of T2D in a multiethnic population and this study was conducted in Canada . Ralston et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…suggested that odd‐chained SFA may be negatively associated with T2D, our results indicate this as well . To our knowledge, only one previous study investigated the association between individual FAs and T2D or metabolic markers of T2D in a multiethnic population and this study was conducted in Canada . Ralston et al.…”
Section: Discussionmentioning
confidence: 99%
“…The association of plasma CEFA levels with T2D in the overall population and per ethnic group was investigated using logistic regression and presented as odds ratios with their corresponding 95% confidence interval (OR [95% CI]). We investigated whether the association between CEFA and T2D differed by sex by adding an interaction term between CEFA and sex in our models, due to indications that the association between FAs and T2D may be sex specific . No evidence for interaction by sex was found (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dose of fatty acids was found to have no cytotoxic or deleterious effects on cell viability, as evaluated by membrane integrity and DNA fragmentation (data not shown). Importantly, we chose for the in vitro experiments a dose of palmitoleic acid higher than that found in plasma of humans and/or rodents (8,26,31,32), because, in contrast to regular adipocytes, palmitoleic acid is the most abundant fatty acid in differentiated 3T3-L1 cells (11,35). Thus, a higher dose of palmitoleic acid is required to challenge these cells.…”
Section: Methodsmentioning
confidence: 98%
“…6 Lee et al 7 found that Taiwanese immigrants who lived in Australia for >5 years had higher insulin and HOMA compared with immigrants who had lived in Australia <5 years. Similarly, among immigrants to Canada, Chiu et al 8 found poorer risk factor profiles, including diabetes as an indicator, with longer dura-Acculturation and Insulin Resistance -Tseng and Fang these are potentially associated with both acculturation 7 and insulin resistance 33 and may suggest an alternative mechanism linking the two.…”
Section: Acculturation and Insulin Resistance -Tseng And Fangmentioning
confidence: 97%